Transesophageal echocardiography guidance for percutaneous closure of PFO and a new method to improve the diagnosis and safety during the procedures - Luo, Limin; Xie, Zehan; Wu, Qiaoyan; Liu, Qiang; Hou, Huiping; Wang, Yongshi; Shu, Xianhong (Frontiers in Cardiovascular Medicine, 2024)
Percutaneous patent foramen ovale (PFO) closure is becoming more and more common for the treatment or prevention of PFO-associated right-toleft shunt (RLS). This study aims to investigate the value of transesophageal echocardiography (TEE) in percutaneous PFO closure, and to explore a new method that can improve intraoperative diagnosis and surgical safety.The application of TEE during the procedure of percutaneous PFO closure, including preoperative evaluation, intraoperative guidance, and postoperative reevaluation, can offer further details about the anatomical and shunt characteristics of PFO, improve the diagnosis rate, and confirm the safety of the surgical path. It ensures the safety and reliability of the whole operation, greatly improving the success rate and reducing postoperative complications.Conclusions: TEE guidance of percutaneous PFO closure has the advantages of minimal trauma, no radiation and real-time visualization, while injecting heparinized sterile saline through the delivery sheath is safer and more effective in improving the success rate and reducing postoperative complications.